Destino ambiental de los Tecno-fósiles agrícolas del cantón Latacunga Provincia de Cotopaxi en el periodo 2020-2021 - Atiencia Chamorro, Juan Carlos (2021)
Plastic films used in agriculture have progressively deteriorated, losing their mechanical and spectro-radiometric properties, requiring frequent replacement. At the end of their useful life, plastic waste is often burnt in open fields, abandoned in fields or watercourses, buried in the soil or disposed of in landfills, releasing harmful substances and pollutants into the air, contaminating food, affecting soil quality, causing visual pollution, landscape, and agro-ecosystem degradation. This study was carried out to establish the environmental fate of agricultural techno-fossils in the agro-industrial zone of Latacunga canton, including its urban and rural parishes. The objective was to identify the environmental fate of plastic films used in agricultural production undercover in the canton of Latacunga. For this purpose, the spatial distribution of agricultural plastic film use in the canton of Latacunga was determined based on unsupervised classification using land cover maps from the Google Earth platform. The final destinations of discarded agricultural plastic films were identified by applying specific surveys and interviews with producers and managers of particular waste. Finally, sustainable film management mechanisms were detailed. Images from the Google Earth platform were used to identify and classify the areas dedicated to plasticulture in the QGIS program. We found 938.06 ha of crops under the plastic cover; most of them correspond to agro-industrial companies dedicated to cultivating high economic value crops, the leading flowers for export in the Latacunga canton. In order to manage particular plastic sheeting waste, informal management systems have been developed, which allow for the recycling of around 90% of the plastics generated in greenhouses registered with the managers. The collection processes, raw material collection, and pre-washing are carried out in local collection centers. A specialized management company carries out washing, drying and baling, processing, distribution, and marketing. The primary purpose of the managed plastic waste was to recycle films as raw material for the production of agricultural inks. The proposed sustainable management processes focus on including all stakeholders (producers, consumers, and various public and private entities), favoring the adequate energy recovery of the recovered materials and the sustainability of plasticulture.